1990
DOI: 10.1002/jez.1402550106
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate and plasma corticosterone levels in juvenile alligators maintained at different stocking densities

Abstract: Sixty-six captive-reared, juvenile alligators maintained in environmentally controlled chambers were randomly assigned to four treatments consisting of stocking densities of 0.35, 0.18, 0.12, and 0.09 m'/alligator. Alligators were maintained at these densities for 3.5 months. At approximately 4 week intervals the alligators were weighed, measured, and bled via cardiac puncture. Duplicate aliquots of plasma were assayed for corticosterone. All of the alligators continued to grow during the experiment, but allig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 10 publications
2
38
0
2
Order By: Relevance
“…In captivity, very low stocking rates are usually not the norm due to the cost of space, while high stocking densities are avoided to reduce fighting and therefore injuries (Huchzermeyer, 2003). Crowding of juvenile crocodilians also inhibits maximum growth and this behaviour is associated with chronically elevated plasma corticosterone levels (Elsey et al, 1990). From an endocrinological perspective, a recent study on Saltwater crocodiles (Crocodylus porosus) by Isberg and Shilton (2013) shows no difference in plasma corticosterone concentrations between individually and communally housed animals.…”
Section: Discussionmentioning
confidence: 99%
“…In captivity, very low stocking rates are usually not the norm due to the cost of space, while high stocking densities are avoided to reduce fighting and therefore injuries (Huchzermeyer, 2003). Crowding of juvenile crocodilians also inhibits maximum growth and this behaviour is associated with chronically elevated plasma corticosterone levels (Elsey et al, 1990). From an endocrinological perspective, a recent study on Saltwater crocodiles (Crocodylus porosus) by Isberg and Shilton (2013) shows no difference in plasma corticosterone concentrations between individually and communally housed animals.…”
Section: Discussionmentioning
confidence: 99%
“…cursor cholesterol, 4) modification of the enzymes required for steroidogenesis (e.g., aromatase, cytochrome P450SCd, and 5) modifications of the cellular receptor numbers and function (51). Peterson et al (20) reported a decrease in plasma testosterone concentration in rats exposed in utero to small concentrations (0.064 mg/kg) of dioxin.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive development of alligators from a contaminated and a control Lake in (2)(3)(4)(5). The American alligator (Alligator mississippiensis) was listed as an endangered species in the early 1970s, but populations throughout the southeastern United States grew rapidly after federal protection was instituted (6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alligators from either sham or experimental treatments (see below) were randomly distributed amongst tanks. In order to avoid density-dependent growth effects (Elsey et al, 1990), density was progressively decreased from hatching (~16 alligatorsm -2 ) until they were sacrificed (~4 alligatorsm -2 ), as alligators grew. In addition, animals were housed in tanks based on body mass (e.g.…”
Section: Animal Maintenancementioning
confidence: 99%